Primary Head Teachers’ Construction and Re-negotiation of Care in COVID-19 Lockdown in Scotland - Ferguson, Peter; McKenzie, Megan; Mercieca, Daniela; Mercieca, Duncan P.; Sutherland, Lesley (Frontiers in Education, 2021)
This paper looks at three primary Head Teachers’ experience of working in COVID-19 lockdown in Scotland. The theoretical framework of this paper builds on Nel Noddings’ ethics of care, with a particular focus on reciprocity, empathy, communication and community. The three Head Teachers were interviewed during the pandemic lockdown. These interviews are part of a larger study that interviewed teachers and Head Teachers during COVID-19 lockdown in Scotland, asking how this lockdown challenged and influenced their identity as educators. The focus on care is important as during lockdown in Scotland the focus of home learning was on pupils and families’ wellbeing and care, rather than on performative acts of learning. This paper argues that the pandemic provided an alternative space for the Head Teachers to re-negotiate their caring role and identity in their understanding of being an educational leader.